Review of Noyce, Küssner and Sollich: Quantifying Shapes - M, Daniel (Empirical Musicology Review, 2013)
This review discusses the original contributions and strengths of the target article by Noyce, Küssner and Sollich and also suggests a few points for consideration to maximize the usefulness of their analytical approach for the music psychology research community.